DETERMINATION OF THE BEST ROSELLA (Hibiscus sabdarifa L.) FILTRATE CONCENTRATION IN EGG YOLK CITRATE DILUENT - Arman Sayuti; Herdina Mayuri; Nuzul Asmilia; Tazul Arifin; Mulyadi Adam (Jurnal Kedokteran Hewan, 2021)
The aim of this research was to determine if the substitution of rosella filtrate (Hibiscus sabdarifa L.) in citrate-based diluent and egg yolks with the ratio 4:1 (16 mL citrate + 4 mL yolk) would help maintain the progressive motility of Kacang goat spermatozoa at room temperature. This study used a male Kacang goat with an average sperm quality of approximately ≥ 205 x 107 spermatozoa/mL and motility of 81.6%. An electro-ejaculator was used once a week to collect the semen. The treatments were labelled as follows: P0 was the negative control group, treatment P1 was given 5% rosella filtrate, treatment P2 was given 10% rosella filtrate, and treatment P3 was given 15% rosella filtrate. Examination of the motility of the spermatozoa was carried out at room temperature. The examination was carried out once every four hours. It was concluded that the rosella filtrate could maintain the progressive motility of spermatozoa of the Kacang goat at optimal concentrations. The optimal motility percentage was found at a concentration of 15% at a storage life of 0-4 hours.